Facet-dependent Catalysis of CuNi Nanocatalysts toward 4–Nitrophenol Reduction Reaction. (2020) - Li, Can; Luan, Yiliang; Zhao, Bo; Kumbhar, Amar; Chen, Xiaobo; Collins, David; Zhou, Guangwen; Fang, Jiye
ABSTRACT: We report a facile method to fabricate CuNi nano-octahedra and nanocubes using a colloidal synthesis approach. The CuNi nanocrystals terminated with exclusive crystallographic facets were controlled and achieved by a group of synergetic capping ligands in a hot solution system. Specifically, the growth of 111-bounded CuNi nano-octahedra is derived by a thermodynamic control, whereas the generation of 100-terminated CuNi nanocubes is steered by a kinetic capping of chloride. Using a reduction of 4-nitrophenol with sodium borohydride as a model reaction, CuNi nano-octahedra and nanocubes demonstrated a strong facet-dependence due to their different surface energies although both exhibited remarkable catalytic activity with the high rate constant over mass (k/m). A kinetic study indicated that this is a pseudo first-order reaction with an excess of sodium borohydride. CuNi nanocubes as the catalysts showed better catalytic performance (k/m = 385 s -1 g -1 ) than the CuNi nano-octahedra (k/m = 120 s -1 g -1 ), indicating that 4-nitrophenol and hydrogen were adsorbed on the 100 facets with their molecules parallel to the surface much easier than those on 111 facets.